TINJAUAN KELAYAKAN KOTA PARIAMAN SEBAGAI HEALTHY CITY TERHADAP INFRASTUKTUR DRAINASE DAN RUANG TERBUKA HIJAU PUBLIK DI KOTA PARIAMAN - alfarezi alfarezi revindo; Iswandi Umar (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
Nowadays, the physical changes of the city which are quite rapid and developing are also happening in Pariaman City, a city located in a strategic area that makes it easier for city development to trigger the rapid development of infrastructure development. Pariaman city is one of the cities that has a vision and mission plan in the target to make it a healthy city or a healthy city in urban infrastructure, especially in drainage and public green open space (RTH). In the goal of achieving a healthy city, it is necessary to conduct an assessment of an object that is seen from a problem that occurs in a city. So it is necessary to conduct a review to determine whether the city of Pariaman is a healthy city in the infrastructure. This research aims to (1) To determine the feasibility of drainage infrastructure and the availability of public green open space (RTH) in a health city in Pariaman City. (2) Knowing the distribution of drainage infrastructure and public green open space (RTH) in a health city in Kota Pariaman. This research method is divided into two parts (1) Drainage by using a weighting / scoring technique so that the results of the summation will show the drainage eligibility criteria. (2) Public Green Open Space (RTH) by using google maps satellite image interpretation techniques. Based on the results of calculations and summation of drainage and public green open space (RTH), it can be seen that: (1) The final assessment of each sub-district in Pariaman City shows that the average drainage is quite decent, where for the middle Pariaman District the value is 323, East Pariaman District the value is 180, The value of North Pariaman District is 170 and South Pariaman District is 173. (2) The distribution of drainage in Pariaman city shows different categories in each sub-district. So that the average distribution of drainage in the inner city of Pariaman is quite feasible. (3) Based on the analysis results for the availability of public green open space in Pariaman City in accordance with the Minister of Public Works No.05/PRT/M/2008 for the need for public green open space must be 20%. So from the analysis obtained, it shows that Kota Pariaman has met the standard for public green open space, namely 151,391 ha if the percentage is 21.00% of the total area in urban areas. (4) Central Pariaman District has an area of ​​397.82 ha, East Pariaman District has an area of ​​158.23 ha, North Pariaman District has an area of ​​41,598 ha and South Pariaman District has an area of ​​442.51 ha. The most dominant type of public green open space in Pariaman City is urban agricultural green open space.